Цукровий діабет і вагітність: між бажаним і дійсним - Medved, V.I.; Islamova, E.V.; Bykova, L.M.; Danylkiv, O.E.; Danylko, V.A.; Shkabarovska, O.M. (Ендокринологія | Endokrynologia, 2020)
Цукровий діабет і вагітність: між бажаним і дійсним